2014
DOI: 10.1111/jpi.12119
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin treatment induces interplay of apoptosis, autophagy, and senescence in human colorectal cancer cells

Abstract: In Asia, the incidence of colorectal cancer has been increasing gradually due to a more Westernized lifestyle. The aim of study is to determine the interaction between melatonin-induced cell death and cellular senescence. We treated HCT116 human colorectal adenocarcinoma cells with 10 μm melatonin and determined the levels of cell death-related proteins and evaluated cell cycle kinetics. The plasma membrane melatonin receptor, MT1, was significantly decreased by melatonin in a time-dependent manner, whereas th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
113
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 74 publications
9
113
0
Order By: Relevance
“…For example, melatonin upregulates Bax and the conversion of caspase-3 to cleaved form in human colorectal cancer cells [15]. Melatonin also promotes Bcl-2 down-regulation [10], suggesting that it may be an important endogenous cell death modulator.…”
Section: Activation Of Intrinsic and Extrinsic Apoptotic Pathwaysmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, melatonin upregulates Bax and the conversion of caspase-3 to cleaved form in human colorectal cancer cells [15]. Melatonin also promotes Bcl-2 down-regulation [10], suggesting that it may be an important endogenous cell death modulator.…”
Section: Activation Of Intrinsic and Extrinsic Apoptotic Pathwaysmentioning
confidence: 99%
“…Antiproliferative effects delaying the entrance of cells into the S phase) or by arresting cells in the G2/M phase [15]. Prolonging G1 and delaying progression to S phase is one way that melatonin drives tumor cells to become more differentiated.…”
Section: Melatonin Oncostasismentioning
confidence: 99%
“…Since then, this pineal neurohormone Mel has been repeatedly described as a potential anti-cancer molecular tool given its demonstrated pro-apoptotic effect and oncostatic action towards different cancer cell lines (Bizzarri et al, 2013;Perdomo et al, 2013;Rodriguez et al, 2013;Hong et al, 2014), therefore contributing to cancer protection (Hrushesky et al, 2009;Mao et al, 2010;Bukowska, 2011;Santoro et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, Kubatka et al (2001) demonstrated the anti-tumor action of Mel in breast cancer in vivo, and this effect was then confirmed in clinical studies showing its protective effect from mammary carcinogenesis (Nowfar et al, 2002) and in other neoplastic diseases (Hong et al, 2014;Wu et al, 2015).…”
Section: Introductionmentioning
confidence: 95%
“…Melatonin gel treatment in the mouth, which was observed to reduce intestinal morpho-pathological changes [17], is therefore also associated with improved preservation of both small intestinal and oral mucosa. including breast, endometrial, prostate, colon and ovarian cancers as well as choriocarcinoma, melanoma, neuroblastoma and osteosarcoma among others [109][110]. Its oncostatic mechanisms are associated with several hallmarks of cancer.…”
Section: B) Use Of Melatonin In the Prevention Of Radiation-induced Mmentioning
confidence: 99%